Polarizing plate, and image display device using the polarizing plate

The polarizer, with a thin total thickness and specific protective and adhesive layers, addresses the issues of air bubbles and environmental reliability in image display devices, ensuring effective suppression of air bubbles and maintaining high reliability in high temperature and humidity conditions.

JP2025060849AInactive Publication Date: 2025-04-10NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024229271
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polarizing plates with through holes filled with adhesive in image display devices often suffer from air bubbles, especially when the adhesive thickness is reduced, and are prone to decoloration in high temperature and high humidity environments.

Method used

A polarizer with a total thickness of 70 μm or less, featuring through holes, is designed with a first protective layer comprising a resin film and a hard coat layer, and a second protective layer with controlled moisture permeability, along with a pressure-sensitive adhesive layer, to suppress air bubbles and ensure reliability in high temperature and humidity conditions.

Benefits of technology

The solution effectively suppresses air bubbles in the through holes, maintains high reliability in high temperature and humidity environments, and prevents imperfections in conduction when applied to image display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060849000001_ABST
    Figure 2025060849000001_ABST
Patent Text Reader

Abstract

To provide a polarizing plate which is thin and has a through hole, suppresses air bubbles when the through hole is filled with an adhesive, is excellent in reliability under a high temperature and high humidity environment, and can suppress defects of conduction when applied to an image display device.SOLUTION: A polarizing plate has: a polarizer; a first protective layer which is arranged on one side of the polarizer, and includes a resin film and a hard coat layer formed on a side opposite to the polarizer of the resin film; a second protective layer which is arranged on the other side of the polarizer; and an adhesive layer which is provided on a side opposite to the polarizer of the second protective layer. A total thickness of the polarizing plate is 70 μm or less, and the through hole is formed in the polarizing plate. A thickness of the polarizer is 12 μm or less; a thickness of the first protective layer is 29 μm or less and moisture permeability thereof is 200 g / m2 24h to 500 g / m2 24; moisture permeability of the second protective layer is less than 100 g / m2 24h; and a thickness of the adhesive layer is 12 μm to 17 μm and a surface resistance value thereof is 1.0×108 Ω / sq. to 2.0×109 Ω / sq.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate and an image display device using the polarizing plate. [Background technology]

[0002] Polarizing plates are widely used in image display devices such as mobile phones and notebook personal computers to realize image display and / or improve the performance of the image display. In recent years, image display devices equipped with cameras have come to be widely used due to the rapid spread of smartphones and touch panel type information processing devices. Correspondingly, polarizing plates having through holes at positions corresponding to the camera parts have also come to be widely used. The through holes are typically filled with an adhesive for laminating a cover glass. In image display devices including polarizing plates in which the through holes are filled with an adhesive, air bubbles may occur in the through hole portions. Such air bubbles become more prominent as the thickness of the adhesive filling the through holes becomes thinner. In order to suppress such air bubbles, attempts have been made to make the polarizing plate (effectively the through holes) thinner. As one attempt at making the polarizing plate thinner, a technology has been proposed in which the protective layer on the adhesive side of the polarizing plate is omitted. However, such a technology has a problem in that discoloration is not possible in high temperature and high humidity environments. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2017 / 047510 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and its main object is to provide a thin polarizing plate having through holes, which suppresses air bubbles when the through holes are filled with an adhesive, has excellent reliability in high temperature and high humidity environments, and can suppress conduction problems when applied to an image display device. [Means for solving the problem]

[0005] A polarizing plate according to an embodiment of the present invention comprises a polarizer; a first protective layer disposed on one side of the polarizer and including a resin film and a hard coat layer formed on the resin film opposite the polarizer; a second protective layer disposed on the other side of the polarizer; and a pressure-sensitive adhesive layer provided on the second protective layer opposite the polarizer. The polarizing plate has a total thickness of 70 μm or less, and a through hole is formed in the polarizing plate. The polarizer has a thickness of 12 μm or less; the first protective layer has a thickness of 29 μm or less, and has a moisture permeability of 200 g / m 2 24h~500g / m 2 24h; the moisture permeability of the second protective layer is 100g / m 2 The thickness of the pressure-sensitive adhesive layer is 12 μm to 17 μm, and the surface resistance is 1.0 × 10 8 Ω / □~2.0×10 9 It is Ω / □. In one embodiment, the hard coat layer has a thickness of 5 μm or less. In one embodiment, the hard coat layer is a cured layer of a resin composition containing a hexa- or higher functional urethane acrylate, tricyclodecane dimethanol dimethacrylate, and a photopolymerization initiator. In one embodiment, the resin composition contains the hexa- or higher functional urethane acrylate and the tricyclodecane dimethanol dimethacrylate in a ratio of 60 / 40 (weight ratio) to 40 / 60 (weight ratio). In one embodiment, the resin film of the first protective layer is a triacetyl cellulose film, and the second protective layer is composed of a cycloolefin-based resin film. In one embodiment, the through hole has a diameter of 5 mm or less. According to another aspect of the present invention, there is provided an image display device comprising an image display cell, the above polarizing plate attached to the viewing side of the image display cell via the pressure-sensitive adhesive layer, and another pressure-sensitive adhesive layer disposed on the viewing side of the polarizing plate, the through-holes of the polarizing plate being filled with the pressure-sensitive adhesive constituting the other pressure-sensitive adhesive layer. In one embodiment, the another pressure-sensitive adhesive layer has a thickness of 120 μm or less. In one embodiment, the image display device further comprises a cover glass on the viewing side of the other pressure-sensitive adhesive layer. In one embodiment, the image display device has a camera unit at a position corresponding to the through hole of the polarizing plate. Effect of the Invention

[0006] According to an embodiment of the present invention, it is possible to realize a polarizing plate that is thin, has through holes, suppresses air bubbles when the through holes are filled with an adhesive, and has excellent reliability in high temperature and high humidity environments (for example, small change in polarization degree, suppressed discoloration of the edges, small change in surface resistance value of the adhesive layer, and suppressed peeling from the image display cell), and can suppress electrical conductivity problems when applied to an image display device. [Brief description of the drawings]

[0007] [Figure 1] 3 is a schematic cross-sectional view of a main portion in the vicinity of a through-hole in a polarizing plate according to one embodiment of the present invention. [Diagram 2] 3 is a schematic cross-sectional view of a main part in the vicinity of a through-hole of a polarizing plate in an image display device according to one embodiment of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, specific embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. Note that the drawings are schematic for ease of viewing, and the ratios of length, width, thickness, and the like, as well as angles, etc. in the drawings are different from the actual ones.

[0009] A. Overall structure of polarizing plate FIG. 1 is a schematic cross-sectional view of a main part of a polarizing plate according to one embodiment of the present invention, in the vicinity of a through hole. The polarizing plate 100 of the illustrated example has a polarizer 10; a first protective layer 20 arranged on one side of the polarizer 10; a second protective layer 30 arranged on the other side of the polarizer 10; and an adhesive layer 40 provided on the second protective layer 30 on the opposite side of the polarizer 10. The first protective layer 20 includes a resin film 21 and a hard coat layer 22 formed on the opposite side of the resin film 21 to the polarizer 10. The adhesive layer 40 is used to attach the polarizing plate 100 to an image display cell. For practical purposes, it is preferable that a separator (not shown) is temporarily attached to the surface of the adhesive layer 40 until the polarizing plate is used. By temporarily attaching the separator, the adhesive layer is protected and the polarizing plate can be rolled.

[0010] The polarizing plate 100 has a through hole 50 formed therein. By forming the through hole, for example, when an image display device has a built-in camera, it is possible to prevent adverse effects on the camera performance. The through hole is typically formed at or near the end of the polarizing plate. With such a configuration, when the polarizing plate is applied to an image display device, it is possible to minimize the effects on image display. A plurality of through holes may be provided. In addition, any appropriate shape may be adopted as the planar shape of the through hole depending on the purpose. Specific examples of the planar shape include a circle, an ellipse, a square, a rectangle, a polygon (for example, a pentagon, a hexagon, an octagon), and a combination thereof (for example, a rectangle with a long side or a short side that is an arc). The diameter of the through hole is preferably 10 mm or less, more preferably 8 mm or less, and even more preferably 5 mm or less. The lower limit of the diameter of the through hole may be, for example, 2 mm. According to the embodiment of the present invention, even if the diameter of the through hole is very small, it is possible to satisfactorily suppress air bubbles when filled with an adhesive.

[0011] The total thickness of the polarizing plate is 70 μm or less, preferably 68 μm or less, more preferably 65 μm or less, and even more preferably 62 μm or less. By making the total thickness of the polarizing plate a predetermined value or less, it is possible to significantly suppress air bubbles when the through holes are filled with an adhesive. In particular, even if the thickness of the adhesive (substantially, another adhesive layer described later) is thin, it is possible to significantly suppress air bubbles. The lower limit of the total thickness of the polarizing plate may be, for example, 48 μm. In this specification, the "total thickness of the polarizing plate" means the total thickness of the first protective layer, the polarizer, the second protective layer, and the adhesive layer.

[0012] The thickness of the polarizer is 12 μm or less, preferably 10 μm or less, more preferably 8 μm or less, further preferably 6 μm or less, and particularly preferably 5 μm or less. The lower limit of the thickness of the polarizer may be, for example, 2 μm, or may be, for example, 1 μm. By setting the thickness of the polarizer in this range, it becomes easy to achieve the above total thickness.

[0013] The thickness of the first protective layer is 29 μm or less, and preferably 22 μm to 28 μm. By setting the thickness of the first protective layer in this range, it is easy to achieve the above total thickness. Furthermore, the moisture permeability of the first protective layer is 200 g / m 2 24h~500g / m 2 24h, preferably 220g / m 2 24h~480g / m 2 24h, more preferably 300g / m 2 24h~450g / m 2·24h. If the moisture permeability of the first protective layer is within such a range, a polarizing plate with excellent reliability in a high-temperature, high-humidity environment can be realized. More specifically, a polarizing plate with a small change in the degree of polarization in a high-temperature, high-humidity environment (for example, a change of 0.02% or less in a durability test) can be realized. If the moisture permeability is too large, the reliability in a high-temperature, high-humidity environment may be insufficient. If a film with low moisture permeability (for example, a cyclic olefin resin (COP) film) is used for the first protective layer, cracks may occur near the through-holes due to the difference in linear expansion coefficient with the polarizer in a high-temperature environment (for example, a severe high-temperature environment such as a heat shock test). The thickness and moisture permeability of the first protective layer respectively refer to the thickness and moisture permeability of a laminate of a resin film and a hard coat layer.

[0014] The moisture permeability of the second protective layer is 100g / m 2 Less than 24h, preferably 10g / m 2 24h~70g / m 2 24h, more preferably 20g / m 2 24h~50g / m 2 If the moisture permeability is too high, the stability of the surface resistance value of the adhesive layer in a high-temperature and high-humidity environment may become insufficient (for example, the change in the durability test may exceed 10 times). As a result, when the polarizing plate is applied to an image display device, a problem may occur in the electrical continuity of the image display device.

[0015] The thickness of the adhesive layer is 12 μm to 17 μm, and preferably 13 μm to 16 μm. If the thickness is too large, paste dents (a phenomenon in which the adhesive layer is dented) may occur during through-hole processing, resulting in poor appearance, and / or the total thickness of the polarizing plate may become too thick, resulting in air bubbles being generated when the through-holes are filled with an adhesive (effectively, an adhesive constituting another adhesive layer described below). If the thickness is too small, the polarizing plate may peel off from the image display cell in a high-temperature and high-humidity environment. Furthermore, the surface resistance of the adhesive layer is 1.0×10 8 Ω / □~2.0×10 9 Ω / □, preferably 3.0×10 8Ω / □~1.2×10 9 Ω / □, and more preferably 5.0×10 8 Ω / □~1.0×10 9 The surface resistance is Ω / □. If the surface resistance is too low, the touch sensitivity of the display may become excessive, resulting in malfunction. If the surface resistance is too high, the film's conductivity may be poor, making it impossible to remove static electricity that has built up during the manufacturing process, resulting in problems with image display.

[0016] The polarizing plate according to the embodiment of the present invention may be used as a viewer-side polarizing plate or a rear-side polarizing plate. The polarizing plate according to the embodiment of the present invention may be preferably used as a viewer-side polarizing plate. Furthermore, the polarizing plate according to the embodiment of the present invention may further have any appropriate optical functional layer depending on the purpose. Examples of the optical functional layer include a retardation layer, a conductive layer for a touch panel, and a reflective polarizer. The number, type, combination, arrangement position, etc. of the optical functional layer may be appropriately set depending on the purpose.

[0017] The polarizer, the first protective layer, the second protective layer and the pressure-sensitive adhesive layer that constitute the polarizing plate will be specifically described below.

[0018] B. Polarizer A polarizer is typically made of a resin film containing a dichroic material. Any appropriate resin film that can be used as a polarizer can be adopted as the resin film. A typical resin film is a polyvinyl alcohol resin (hereinafter referred to as "PVA resin") film. The resin film may be a single-layer resin film or a laminate of two or more layers.

[0019] A specific example of a polarizer composed of a single-layer resin film is a PVA-based resin film that has been subjected to a dyeing treatment with iodine and a stretching treatment (typically, uniaxial stretching). The dyeing with iodine is performed, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be performed after the dyeing treatment or while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based resin film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based resin film in water and washing it before dyeing, not only can dirt and antiblocking agents on the surface of the PVA-based film be washed off, but also the PVA-based resin film can be swelled to prevent uneven dyeing.

[0020] Specific examples of polarizers obtained using the laminate of two or more layers include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and to achieve high optical properties. In addition, by simultaneously increasing the orientation of the PVA in advance, problems such as a decrease in the orientation of the PVA or dissolution when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules can be disturbed and the orientation can be reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage treatment.The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / polarizer laminate after peeling the resin substrate from the resin substrate / polarizer laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.

[0021] The thickness of the polarizer is as described in section A above.

[0022] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 44.0%, preferably 42.5% to 44.0%, and more preferably 43.0% to 44.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0023] C. First protective layer C-1.Resin film As the resin film, any suitable resin film that can be used as a protective layer for a polarizer can be used as long as the desired moisture permeability can be obtained as the first protective layer. Specific examples of materials that are the main components of the resin film include cellulose-based resins such as triacetyl cellulose (TAC). A film formed from such a resin can be combined with a specific hard coat layer described later to form a first protective layer with an appropriate thickness and the desired moisture permeability.

[0024] The moisture permeability of the resin film is preferably 600 g / m 2 24h~2000g / m 2 24h, more preferably 800g / m 2 24h~1500g / m 2When the moisture permeability of the resin film is within this range, a first protective layer having the desired moisture permeability can be formed by combining with a specific hard coat layer described later.

[0025] The thickness of the resin film is preferably 15 μm to 28 μm, and more preferably 20 μm to 26 μm. If the thickness of the resin film is within this range, the first protective layer having the desired thickness can be formed.

[0026] C-2. Hard coat layer The hard coat layer preferably has excellent surface hardness (e.g., excellent pencil hardness, excellent steel wool scratch resistance), excellent mechanical strength, and excellent light transmittance. The hard coat layer may have any suitable configuration as long as it has such desired properties. The hard coat layer is typically a cured layer of a resin composition containing a curable resin.

[0027] Specific examples of the curable resin include thermosetting resin, ultraviolet curable resin, electron beam curable resin, and two-liquid mixed resin. The ultraviolet curable resin is preferred because it can form a hard coat layer with simple operation and high efficiency. Specific examples of the ultraviolet curable resin include polyester resin, (meth)acrylic resin, urethane resin, amide resin, silicone resin, epoxy resin, and urethane (meth)acrylate resin. The ultraviolet curable resin includes ultraviolet curable monomers, oligomers, and polymers. The resin composition may contain, for example, a (meth)acrylic resin, or may contain, for example, a urethane (meth)acrylate resin, or may contain a combination of these. The hard coat layer may also contain, for example, a copolymer of an oligomer and a monomer having a functional group. Examples of the monomer having a functional group include, for example, a polyfunctional (meth)acrylate. The (meth)acrylate is, for example, bifunctional or more, or, for example, trifunctional or more. Examples of the oligomer having a functional group include, for example, a curable urethane (meth)acrylate. The curable urethane (meth)acrylate is, for example, 6 or more functional, and for example, 8 to 10 functional. In one embodiment, the resin composition contains, relative to 100 parts by weight of the curable resin, preferably 60 parts by weight or more of the curable urethane (meth)acrylate and the polyfunctional (meth)acrylate in total, more preferably 70 parts by weight or more, even more preferably 80 parts by weight or more, particularly preferably 90 parts by weight or more, and particularly preferably 95 parts by weight or more. The total amount may be 100 parts by weight. The blending ratio of the curable urethane (meth)acrylate and the polyfunctional (meth)acrylate in the curable resin is preferably 60 / 40 (weight ratio) to 40 / 60 (weight ratio), more preferably 55 / 45 (weight ratio) to 45 / 55 (weight ratio). In one embodiment, all of the curable resins are composed of 6 or more functional urethane (meth)acrylate and the polyfunctional (meth)acrylate. For example, the curable resin may be composed of 10-functional urethane (meth)acrylate / tricyclodecane dimethanol dimethacrylate (50 / 50: weight ratio).

[0028] The resin composition typically contains a photopolymerization initiator. As the photopolymerization initiator, any appropriate photopolymerization initiator is used depending on the curable resin.

[0029] The resin composition (and thus the hard coat layer) may contain silicon as an element. Silicon may be, for example, a constituent element of a surface conditioner. Thus, the resin composition (and thus the hard coat layer) may contain a surface conditioner (typically, a leveling agent), and the surface conditioner may contain, for example, a silicon compound having a dimethylsiloxane skeleton. The silicon compound may be a dimethylsiloxane-modified methacrylic acid ester, a polydimethylsiloxane cyclic compound, or the like.

[0030] The pencil hardness of the hard coat layer is preferably at least F, more preferably at least H, and even more preferably at least 3H. When the pencil hardness of the hard coat layer is within this range, a sufficient protective function as the outermost layer on the viewing side can be achieved.

[0031] The moisture permeability per unit thickness of the hard coat layer is preferably 100 g / m 2 24hμm~400g / m 2 24h μm, more preferably 120 g / m 2 24hμm~250g / m 2 24h·μm. If the moisture permeability of the hard coat layer is within this range, it is possible to form a first protective layer having the desired moisture permeability by combining it with the specific resin film described above. The moisture permeability per unit thickness of the hard coat layer is the value obtained by subtracting the moisture permeability of the resin film from the moisture permeability of the first protective layer and dividing the result by the thickness of the hard coat layer.

[0032] The haze value of the hard coat layer may be, for example, 5% or more, for example, 10% or more, for example, 15% or more, or for example, 20% or more. On the other hand, the haze value of the hard coat layer may be, for example, 50% or less, for example, 45% or less, for example, 40% or less, or for example, 35% or less. If the haze value is in such a range, the occurrence of shading and reflection from the outside are suppressed, and the deterioration of the display characteristics (for example, clarity, contrast in a dark place) of the image display device can be suppressed. The haze value can be typically measured in accordance with JIS K 7136.

[0033] The thickness of the hard coat layer is preferably 5 μm or less, and more preferably 2 μm to 4 μm. When the thickness of the hard coat layer is within this range, a first protective layer having a desired thickness can be formed while maintaining a desired moisture permeability.

[0034] The hard coat layer can be formed by any suitable method. For example, the hard coat layer can be formed by applying a resin composition for forming a hard coat layer (coating liquid) onto a resin film, drying the applied film, and curing the dried applied film by irradiating it with ultraviolet light.

[0035] D. Second Layer of Protection The moisture permeability of the second protective layer is 100 g / m 2 Less than 24h, preferably 10g / m 2 24h~70g / m 2 24h, more preferably 20g / m 2 24h~50g / m 2 If the moisture permeability of the second protective layer is within this range, the generation of air bubbles is suppressed when the through-holes are filled with an adhesive (described later) constituting another adhesive layer, and the change in the surface resistance value of the adhesive layer in a high-temperature and high-humidity environment can be reduced.

[0036] The second protective layer may be made of any suitable resin film that can be used as a protective layer for a polarizer as long as the desired moisture permeability is obtained. Specific examples of materials that are the main components of the resin film include cycloolefin resins (e.g., norbornene resins).

[0037] The thickness of the second protective layer is preferably 10 μm to 30 μm, and more preferably 10 μm to 16 μm. When the thickness of the second protective layer is within this range, a polarizing plate having the desired characteristics and the desired total thickness can be formed.

[0038] E. Adhesive layer As described above, the adhesive layer is used to attach the polarizing plate to the image display cell. The surface resistance of the adhesive layer is 1.0×10 8 Ω / □~2.0×10 9 Ω / □, preferably 3.0×10 8 Ω / □~1.2×10 9 Ω / □, and more preferably 5.0×10 8 Ω / □~1.0×10 9 If the surface resistance value of the pressure-sensitive adhesive layer is within such a range, it is possible to suppress conduction problems when the polarizing plate is applied to an image display device.

[0039] The adhesive strength of the adhesive layer to glass is preferably 1.5 N / 25 mm or more and less than 5.5 N / 25 mm, more preferably 2.5 N / 25 mm or more and 4.5 N / 25 mm or less, and even more preferably 3.0 N / 25 mm or more and 4.0 N / 25 mm or less. If the adhesive strength is in such a range, the adhesive layer has excellent adhesion to the image display panel and excellent reworkability.

[0040] The pressure-sensitive adhesive layer preferably has a storage modulus at 25° C. of 1.0×10 4 Pa~1.0×10 6 Pa, more preferably 1.0×10 4 Pa~1.0×10 5When the storage modulus of the pressure-sensitive adhesive layer is within this range, it is possible to suppress defects in the appearance of the polarizing plate in a high-temperature and high-humidity environment. The storage modulus can be obtained by dynamic viscoelasticity measurement.

[0041] The creep amount ΔCr of the adhesive layer at 70°C is, for example, 120 μm or less, and may be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, or even 15 μm or less. The lower limit of the creep amount ΔCr is, for example, 0.5 μm. If the creep amount is within such a range, it is possible to suppress the appearance defect of the polarizing plate in a high-temperature and high-humidity environment, as in the case of the storage elastic modulus. The creep value can be measured, for example, by the following procedure: A load of 500 gf is applied vertically downward to the adhesive layer attached to a stainless steel test plate at a joint surface of 20 mm long x 20 mm wide, with the test plate fixed. The creep amount (displacement amount) of the adhesive layer relative to the test plate is measured at each time point 100 seconds and 3600 seconds after the start of the load application, and the Cr 100 and Cr 3600 The measured Cr 100 and Cr 3600 From the formula ΔCr = Cr 3600 -Cr 100 The creep amount ΔCr can be calculated by the following equation.

[0042] The thickness of the adhesive layer is 12 μm to 17 μm, as described above, and preferably 13 μm to 16 μm. If the thickness of the adhesive layer is in this range, peeling in a high-temperature and high-humidity environment can be suppressed, and the generation of air bubbles can be suppressed when the through-holes are filled with an adhesive (described later) constituting another adhesive layer.

[0043] As the adhesive (adhesive composition) constituting the adhesive layer, any appropriate adhesive can be used as long as it can satisfy the above-mentioned characteristics. The adhesive composition typically contains a base polymer and a conductive component.

[0044] Examples of the base polymer include (meth)acrylic polymers, urethane polymers, silicone polymers, and rubber polymers. (Meth)acrylic polymers are preferred. In this specification, the (meth)acrylic polymer as the base polymer may be referred to as a (meth)acrylic base polymer.

[0045] The (meth)acrylic base polymer typically contains an alkyl (meth)acrylate as a main monomer component. The alkyl group of the alkyl (meth)acrylate may be, for example, a linear or branched alkyl group having 1 to 18 carbon atoms. The average number of carbon atoms in the alkyl group is preferably 3 to 9, more preferably 3 to 6. A preferred alkyl (meth)acrylate is butyl acrylate. The content of the alkoxy group-containing monomer in the base polymer is preferably 50 parts by weight or more, more preferably 60 parts by weight or more, even more preferably 70 parts by weight or more, and particularly preferably 80 parts by weight or more, based on 100 parts by weight of the total monomer components. The alkyl (meth)acrylate may be used alone or in combination of two or more kinds.

[0046] The (meth)acrylic base polymer typically contains a monomer component (copolymerizable monomer component) that can be copolymerized with an alkyl (meth)acrylate. Examples of the copolymerizable monomer component include a carboxyl group-containing monomer, a hydroxyl group-containing monomer, an alkoxy group-containing monomer, an amide group-containing monomer, an aromatic ring-containing (meth)acrylate, and a heterocyclic ring-containing vinyl monomer. By appropriately adjusting the type, number, combination, and amount (content) of the copolymerizable monomer, a base polymer (and thus a pressure-sensitive adhesive layer) having desired properties can be obtained. In one embodiment, the (meth)acrylic base polymer may be a copolymer of an alkyl (meth)acrylate (e.g., butyl acrylate), an aromatic ring-containing (meth)acrylate (e.g., phenoxyethyl acrylate), a heterocyclic ring-containing vinyl monomer (e.g., N-vinyl-2-pyrrolidone), a carboxyl group-containing monomer (e.g., acrylic acid), and a hydroxyl group-containing monomer (e.g., 4-hydroxybutyl acrylate).

[0047] The weight average molecular weight Mw of the (meth)acrylic base polymer is preferably 1 million to 3 million, more preferably 1 million to 2 million, and further preferably 1 million to 1.6 million. If the weight average molecular weight Mw is less than 1 million, cracks may not be sufficiently suppressed. If the weight average molecular weight Mw exceeds 3 million, an increase in viscosity and / or gelation during polymer polymerization may occur.

[0048] Representative examples of the conductive component include inorganic cationic salts and organic cationic salts.

[0049] The inorganic cation salt is specifically an inorganic cation-anion salt. The cation constituting the cation part of the inorganic cation salt is typically an alkali metal ion. Specific examples include a lithium ion, a sodium ion, and a potassium ion. The lithium ion is preferred. Therefore, the preferred inorganic cation salt is a lithium salt.

[0050] Examples of anions constituting the anion portion of inorganic cationic salts include Cl. - , Br - , I - , AlCl 4 - , Al 2 Cl 7 - , B.F. 4 - , P.F. 6 - , ClO 4 - , NO 3 - , C.H. 3 COO - , C.F. 3 COO - , C.H. 3 SO 3 - , C.F. 3 SO 3 - , (CF 3 SO 2 ) 3 C - , AsF 6 - , SbF 6 - , NbF 6 - , TaF 6 - , (CN) 2 N - , C 4 F 9 SO 3 - , C 3 F 7 COO - , (CF 3 SO 2 )(CF 3 CO)N - , - O 3 S(CF 2 ) 3 SO 3 - and the following general formulas (1) to (4): (1): (C n F 2n+1 SO 2 ) 2 N -(n is an integer from 1 to 10), (2):CF 2 (C m F 2m SO 2 ) 2 N - (m is an integer from 1 to 10), (3): - O 3 S(CF 2 ) l SO 3 - (l is an integer from 1 to 10), (4): (C p F 2p+1 SO 2 )N - (C q F 2q+1 SO 2 ), (p and q are integers from 1 to 10),

[0033] Fluorine-containing anions are preferred, and fluorine-containing imide anions are more preferred.

[0051] The fluorine-containing imide anion may be, for example, an imide anion having a perfluoroalkyl group. 3 SO 2 )(CF 3 CO)N - and general formulas (1), (2) and (4) (1): (C n F 2n+1 SO 2 ) 2 N - (n is an integer from 1 to 10), (2):CF 2 (C m F 2m SO 2 ) 2 N - (m is an integer from 1 to 10), (4): (C p F 2p+1 SO 2 )N - (C q F 2q+1 SO 2 ), (p and q are integers from 1 to 10), Preferably, the anion is represented by (CF 3 SO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - and the like, more preferably (CF 3 SO 2 ) 2 N - Thus, a preferred inorganic cation salt that can be used in the embodiments of the present invention is lithium bis(trifluoromethanesulfonyl)imide.

[0052] The organic cation salt is specifically an organic cation-anion salt. The cation constituting the cation portion of the organic cation salt is typically an organic onium that forms an onium ion by substitution with an organic group. The onium in the organic onium is, for example, a nitrogen-containing onium, a sulfur-containing onium, or a phosphorus-containing onium. Preferably, the onium is a nitrogen-containing onium or a sulfur-containing onium. The nitrogen-containing onium is, for example, an ammonium cation, a piperidinium cation, a pyrrolidinium cation, a pyridinium cation, a cation having a pyrroline skeleton, a cation having a pyrrole skeleton, an imidazolium cation, a tetrahydropyrimidinium cation, a dihydropyrimidinium cation, a pyrazolium cation, or a pyrazolinium cation. The sulfur-containing onium is, for example, a sulfonium cation. The phosphorus-containing onium is, for example, a phosphonium cation. The organic group in the organic onium is, for example, an alkyl group, an alkoxyl group, or an alkenyl group. Specific examples of preferred organic oniums include tetraalkylammonium cations (e.g., trimethylbutylammonium cations), alkylpiperidinium cations, and alkylpyrrolidinium cations. The anions constituting the anion portion of the organic cation salts are as described for the anions constituting the anion portion of the inorganic cations. Preferred organic cation salts that can be used in the embodiments of the present invention are methylpropylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, and trimethylbutylammonium bis(trifluoromethanesulfonyl)imide.

[0053] An inorganic cationic salt and an organic cationic salt may be used in combination.

[0054] The conductive component may be a solid or a liquid (ie, an ionic liquid).

[0055] The content of the conductive component in the pressure-sensitive adhesive composition is preferably 5 to 15 parts by weight, more preferably 8 to 12 parts by weight, based on 100 parts by weight of the base polymer. When the content of the conductive component is within this range, a desired surface resistance value can be obtained without adversely affecting other properties.

[0056] The pressure-sensitive adhesive composition typically contains a silane coupling agent and / or a crosslinking agent. Typical examples of the silane coupling agent include functional group-containing silane coupling agents. Examples of the functional group include epoxy groups, mercapto groups, amino groups, isocyanate groups, isocyanurate groups, vinyl groups, styryl groups, acetoacetyl groups, ureido groups, thiourea groups, (meth)acrylic groups, heterocyclic groups, acid anhydride groups, and combinations thereof. The functional group-containing silane coupling agents can be used alone or in combination. Examples of the crosslinking agent include isocyanate-based crosslinking agents and peroxide-based crosslinking agents. The crosslinking agents can also be used alone or in combination.

[0057] The adhesive composition may contain additives. Specific examples of additives include colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, UV absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, and foils. In addition, a redox system may be used by adding a reducing agent within a controllable range. The type, number, combination, and content of additives may be appropriately set according to the purpose.

[0058] F. Image display device The polarizing plate according to the embodiment of the present invention may be applied to an image display device. Therefore, the image display device is also included in the embodiment of the present invention. Examples of the image display device include a liquid crystal display device, an organic electroluminescence (EL) display device, and a quantum dot display device. FIG. 2 is a schematic cross-sectional view of a main part of a portion near a through-hole of a polarizing plate in an image display device according to one embodiment of the present invention. The image display device 200 of the illustrated example has an image display cell 120; a polarizing plate 100 bonded to the viewing side of the image display cell 120 via an adhesive layer 40; and another adhesive layer 140 arranged on the viewing side of the polarizing plate 100. The polarizing plate 100 is a polarizing plate according to the embodiment of the present invention described in the above items A to E. In the embodiment of the present invention, the through-hole 50 of the polarizing plate 100 is filled with an adhesive constituting the other adhesive layer 140. The image display device of the illustrated example may further have a cover glass 160 on the viewing side of the other adhesive layer 140, if necessary. The cover glass 160 can be laminated to the image display device (substantially, the polarizing plate 100) via another adhesive layer 140. In one embodiment, the image display device has a camera section (not shown) at a position corresponding to the through hole 50 of the polarizing plate 100. With such a configuration, it is possible to prevent adverse effects on the photographing performance of the camera. As any appropriate configuration can be adopted for the configuration of the side opposite to the viewing side of the image display cell depending on the type of the image display device, a specific description will be omitted.

[0059] Any suitable adhesive can be used as the adhesive constituting the separate adhesive layer 140. Specific examples of adhesives include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base polymer of the adhesive, the compounding amount of the crosslinking agent, the type, number, combination, and compounding ratio of additives, reaction temperature, and reaction time, etc., an adhesive having desired properties according to the purpose can be prepared. The base polymer of the adhesive may be used alone or in combination of two or more types. From the viewpoints of transparency, processability, durability, etc., an acrylic adhesive is preferred.

[0060] The other pressure-sensitive adhesive layer preferably has a storage modulus at 60° C. before curing of 1.0×10 3 Pa~1.0×10 6 Pa, more preferably 1.0×10 4 Pa~1.0×10 5 The storage modulus at 25° C. after curing of the other pressure-sensitive adhesive layer is preferably 1.0×10 4 Pa~1.0×10 7 Pa, more preferably 1.0×10 5 Pa~1.0×10 7 When the storage modulus of the separate pressure-sensitive adhesive layer is within such a range, the layer is soft when bonded and resistant to external stress after curing, and due to a synergistic effect with the effect of the embodiment of the present invention, air bubbles in the through-hole portion can be suppressed even if the layer is thin, as described later.

[0061] The thickness of the separate adhesive layer is preferably 150 μm or less, more preferably 120 μm or less, even more preferably 100 μm or less, and particularly preferably 75 μm or less. According to the embodiment of the present invention, even if the thickness of the separate adhesive layer is so thin, it is possible to realize a polarizing plate that can suppress bubbles in the through-hole portion, has excellent reliability in a high-temperature and high-humidity environment, and can suppress conduction problems when applied to an image display device. The thickness of the separate adhesive layer can be, for example, 50 μm or more. EXAMPLES

[0062] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The evaluation items in the examples are as follows. In addition, unless otherwise specified, "parts" and "%" in the examples are based on weight.

[0063] (1) Air bubbles in the through hole area The polarizing plates obtained in the examples and comparative examples were cut to 150 mm x 70 mm, and a through hole with a diameter of 3 mm was formed so that the top of the through hole was located 3 mm from the upper end in the long side direction. This polarizing plate was attached to a glass plate. A laminate in which an optical adhesive (another adhesive layer, thickness 100 μm, "CEF7104" manufactured by 3M) was provided on a cover glass was attached to the laminate of the polarizing plate / glass plate by vacuum lamination (pressure 0.3 MPa, temperature 60 ° C, 10 minutes) via the optical adhesive, and the through hole part of the polarizing plate was filled with the optical adhesive. Air bubbles in the through hole part were visually observed and evaluated according to the following criteria. ○ (Good): No air bubbles were observed × (bad): Air bubbles were found

[0064] (2) Change in polarization degree under high temperature and humidity conditions The polarizing plates obtained in the examples and comparative examples were attached to a non-alkali glass plate to prepare a measurement sample. The polarization degree P of the measurement sample was measured using a UV-visible spectrophotometer (LPF-200 manufactured by Otsuka Electronics Co., Ltd.). 0 Furthermore, the measurement sample was subjected to a durability test at 65°C and 90% RH for 500 hours, and the polarization degree P 500 was measured. ΔP=P 0 -P 500 was calculated and evaluated according to the following criteria. ○ (Good): ΔP is less than 0.02% × (defective): ΔP is 0.02% or more

[0065] (3) Surface resistance of the adhesive layer and stability of the surface resistance The surface resistance of the adhesive layer of the polarizing plate obtained in the examples and comparative examples was measured using Hiresta UP MCP HT450 (Mitsubishi Chemical Analytech Co., Ltd.). 9 If it exceeds Ω / □, electrical conductivity problems will occur in many image display devices, so if it is below that value, electrical conductivity is judged to be good. Furthermore, the polarizing plate was subjected to a durability test at 60℃ and 90% RH for 500 hours, and the surface resistance of the adhesive layer after the test was measured, and the stability of the surface resistance was evaluated according to the following criteria. ○ (Good): Surface resistance is 2×10 9 Ω / □ or less × (bad): Surface resistance is 2×10 9 Greater than Ω / □

[0066] (4) Peeling of polarizing plate in high temperature and humidity environment The polarizing plates obtained in the examples and comparative examples were cut into 300 mm x 220 mm pieces and attached to non-alkali glass plates to prepare measurement samples. The measurement samples were subjected to a durability test at 60°C and 90% RH for 500 hours, and the state of the polarizing plates after the test was observed and evaluated according to the following criteria. ○ (Good): No peeling is observed, or peeling at the edge is less than 0.3 mm × (Fail): Peeling of 0.3 mm or more was observed at the edge

[0067] (5) Cracks near the through hole The polarizing plates obtained in the examples and comparative examples were cut to 150 mm x 70 mm, and a through hole with a diameter of 3 mm was formed so that the top of the through hole was located 3 mm from the top end in the long side direction. This polarizing plate was attached to a non-alkali glass plate to prepare a measurement sample. The measurement sample was subjected to a heat shock test in which the environment was replaced with 85°C and -40°C for 200 cycles, and the cracks in the through hole part after the test were observed and evaluated according to the following criteria. ○ (Good): The maximum size of the crack near the through hole is 300 μm or less. × (Fail): The maximum size of the crack near the through hole is greater than 300 μm.

[0068] <Production Example 1: Preparation of adhesive layer> A monomer mixture containing 80.3 parts of butyl acrylate, 16 parts of phenoxyethyl acrylate, 3 parts of N-vinyl-2-pyrrolidone (NVP), 0.3 parts of acrylic acid, and 0.4 parts of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts by weight of ethyl acetate per 100 parts of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the nitrogen gas. The liquid temperature in the flask was kept at around 55°C, and a polymerization reaction was carried out for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 1.5 million. For 100 parts of the solid content of the obtained acrylic polymer solution, 8.5 parts of EMI-FSI (1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, an ionic liquid manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was blended as a conductive agent (antistatic agent), and further, 0.2 parts of an isocyanate crosslinking agent (trade name: Takenate D160N, trimethylolpropane hexamethylene diisocyanate, manufactured by Mitsui Chemicals, Inc.), 0.25 parts of benzoyl peroxide (trade name: Niper BMT 40SV, manufactured by Nippon Oil & Fats Co., Ltd.), 0.2 parts of a silane coupling agent (manufactured by Soken Chemical Co., Ltd.: A-100), and 0.3 parts of an antioxidant (trade name: Irganox 1010, hindered phenol type, manufactured by BASF Japan Ltd.) were blended to obtain a pressure-sensitive adhesive composition I.

[0069] Next, the adhesive composition I was applied to one side of a polyethylene terephthalate film (separator film: MHE38, manufactured by Mitsubishi Chemical Polyester Film Corporation) that had been treated with a silicone-based release agent, so that the adhesive layer would have a thickness of 15 μm after drying, and dried at 155° C. for 1 minute to form an adhesive layer A with a thickness of 15 μm on the surface of the separator film.

[0070] <Production Example 2: Preparation of adhesive layer> A 10 μm-thick adhesive layer B was formed on the surface of a separator film in the same manner as in Production Example 1, except that the coating thickness of the adhesive composition I was changed.

[0071] <Production Example 3: Preparation of adhesive layer> A pressure-sensitive adhesive composition II was obtained in the same manner as in Production Example 1, except that 20 parts of TBMA-TFSI (tributylmethylammonium bis(trifluoromethane)sulfonimide, an ionic liquid manufactured by 3M, FC-4400) was used instead of 8.5 parts of EMI-FSI. A pressure-sensitive adhesive layer C having a thickness of 15 μm was formed on the surface of a separator film in the same manner as in Production Example 1, except that the pressure-sensitive adhesive composition II was used.

[0072] <Production Example 4: Preparation of adhesive layer> A 20 μm-thick adhesive layer D was formed on the surface of a separator film in the same manner as in Production Example 1, except that the coating thickness of the adhesive composition I was changed.

[0073] <Production Example 5: Preparation of adhesive layer> Except for changing the blending amount of EMI-FSI from 8.5 parts to 6.0 parts, a pressure-sensitive adhesive composition III was obtained in the same manner as in Production Example 1. Except for using the pressure-sensitive adhesive composition III and changing the coating thickness, a pressure-sensitive adhesive layer E having a thickness of 20 μm was formed on the surface of a separator film in the same manner as in Production Example 1.

[0074] <Production Example 6: Preparation of Resin Composition for Forming Hard Coat Layer> 50 parts by weight (solid content equivalent) of ultraviolet-curable acrylate resin (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name "A-DCP", solid content 100%), 50 parts by weight (solid content equivalent) of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Co., Ltd., trade name "UV-1700TL", solid content 80%), 5 parts by weight of photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907"), and 0.1 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., trade name "LE-303", solid content 40%) were mixed. This mixture was diluted with a methyl isobutyl ketone (MIBK) / cyclopentanone mixed solvent (weight ratio 60 / 40) so that the solid content concentration was 30%, to prepare a hard coat layer forming resin composition (coating liquid) A. It should be noted that "A-DCP" is tricyclodecane dimethanol dimethacrylate, and "UV-1700TL" is a 10-functional urethane acrylate. The hard coat layer formed from the coating liquid A is referred to as a hard coat layer A.

[0075] <Production Example 7: Preparation of resin composition for forming hard coat layer> 40 parts by weight of ultraviolet-curable acrylate resin (manufactured by Toa Gosei Co., Ltd., product name "M-920", solid content 100%), 60 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Corporation, product name "UV-1700TL", solid content 80%), 3 parts by weight of photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907"), and 0.2 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., product name "LE-303", solid content 40%) were mixed. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 70 / 30) so that the solid content concentration was 30%, to prepare a hard coat layer forming resin composition (coating liquid) B. Note that "M-920" is glycerin triacrylate. The hard coat layer formed from coating liquid B is referred to as hard coat layer B.

[0076] <Production Example 8: Preparation of Resin Composition for Forming Hard Coat Layer> 100 parts by weight of ultraviolet-curable urethane acrylate (DIC Corporation, product name "UNIDIC 17-806", solid content 80%), 3 parts by weight of photopolymerization initiator (BASF, product name "OMNIRAD907"), and 0.01 parts by weight of leveling agent (DIC Corporation, product name "PC4100", solid content 40%) were mixed. This mixture was diluted with a propylene glycol monomethyl ether (PGM) / cyclopentanone mixed solvent (weight ratio 63 / 37) so that the solid content concentration was 36%, to prepare a hard coat layer forming resin composition (coating liquid) C. The hard coat layer formed from coating liquid C is referred to as hard coat layer C.

[0077] <Example 1> As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a laminate having a resin substrate / polarizer structure was obtained.

[0078] A triacetyl cellulose (TAC) film (thickness: 25 μm) was prepared as the resin film for the first protective layer. Coating solution A of Production Example 6 was applied to this TAC film, and the coating film was heated at 60° C. for 1 minute to dry, and then exposed to a high-pressure mercury lamp with an integrated light quantity of 260 mJ / cm 2 . 2 The coating film was cured by irradiating with ultraviolet light of 1000 nm to form a hard coat (HC) layer A having a thickness of 3 μm. In this way, an HC-TAC film was obtained as a first protective layer. An HC-TAC film was attached as a first protective layer to the polarizer surface (the surface opposite to the resin substrate) of the laminate obtained above. The HC-TAC film was attached so that the TAC film was on the polarizer side. Next, the resin substrate was peeled off, and a cyclic olefin resin (COP) film (thickness 13 μm) was attached as a second protective layer to the peeled surface. Furthermore, the adhesive layer A (thickness 15 μm) of Production Example 1 was transferred to the COP film surface. In this way, a polarizing plate having a configuration of the first protective layer (HC layer A / TAC film) / polarizer (5 μm) / second protective layer (COP film) / adhesive layer A was obtained. The obtained polarizing plate was subjected to the above evaluations (1) to (5). The results are shown in Table 1.

[0079] <Example 2> A long polyvinyl alcohol (PVA) resin film was impregnated with iodine and uniaxially stretched in the longitudinal direction (MD direction) to produce a polarizer (thickness 12 μm). A polarizing plate having through holes was obtained in the same manner as in Example 1, except that this polarizer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0080] <Comparative Examples 1 to 9> A polarizing plate was prepared having the configuration shown in Table 1. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0081] [Table 1]

[0082] The unit of thickness in Table 1 is "μm" and the unit of moisture permeability is "g / m 2 -24h".

[0083] As is clear from Table 1, the polarizing plate according to the embodiment of the present invention is thin, has reduced air bubbles in the through-holes, and has excellent reliability in high-temperature and high-humidity environments (specifically, the change in polarization degree is small, the change in the surface resistance value of the adhesive layer is small, and peeling from the image display cell is suppressed). Furthermore, from the surface resistance value of the adhesive layer, it is understood that the polarizing plate according to the embodiment of the present invention can suppress conduction problems when applied to an image display device. [Industrial Applicability]

[0084] The polarizing plate according to the embodiment of the present invention can be suitably used in image display devices, and in particular, can be suitably used in image display devices having a camera unit, such as smartphones, tablet PCs, or smart watches. [Explanation of symbols]

[0085] 10 Polarizer 20 First protective layer 21 Resin film 22 Hard coat layer 30 Second layer of protection 40 Adhesive layer 50 Through hole 100 Polarizing Plate 120 Image display cells 140 Another adhesive layer 200 Image display device

Claims

1. a first protective layer disposed on one side of the polarizer and including a resin film and a hard coat layer formed on the resin film opposite the polarizer; a second protective layer disposed on the other side of the polarizer; and a pressure-sensitive adhesive layer provided on the second protective layer opposite the polarizer; The total thickness is 70 μm or less, A through hole is formed, The thickness of the polarizer is 12 μm or less, The first protective layer has a thickness of 29 μm or less and a moisture permeability of 200 g / m 2 ・24h~500g / m 2 - 24 hours, The second protective layer has a moisture permeability of 100 g / m 2 - Less than 24 hours The thickness of the pressure-sensitive adhesive layer is 12 μm to 17 μm, and the surface resistance is 1.0×10 8 Ω / □~2.0×10 9 Ω / □, Polarizing plate.

2. The polarizing plate according to claim 1 , wherein the hard coat layer has a thickness of 5 μm or less.

3. 3. The polarizing plate according to claim 2, wherein the hard coat layer is a cured layer of a resin composition containing a hexa- or higher functional urethane acrylate, tricyclodecane dimethanol dimethacrylate, and a photopolymerization initiator.

4. 4. The polarizing plate according to claim 3, wherein the resin composition contains the hexa- or higher functional urethane acrylate and the tricyclodecane dimethanol dimethacrylate in a ratio of 60 / 40 (weight ratio) to 40 / 60 (weight ratio).

5. 5. The polarizing plate according to claim 1, wherein the resin film of the first protective layer is a triacetyl cellulose film, and the second protective layer is composed of a cycloolefin resin film.

6. 6. The polarizing plate according to claim 1, wherein the through holes have a diameter of 5 mm or less.

7. an image display cell; the polarizing plate according to any one of claims 1 to 6 attached to a viewing side of the image display cell via the pressure-sensitive adhesive layer; and another pressure-sensitive adhesive layer disposed on the viewing side of the polarizing plate; the through-holes of the polarizing plate are filled with the pressure-sensitive adhesive constituting the other pressure-sensitive adhesive layer; Image display device.

8. The image display device according to claim 7 , wherein the thickness of the another pressure-sensitive adhesive layer is 120 μm or less.

9. The image display device according to claim 7 , further comprising a cover glass on the viewing side of the other pressure-sensitive adhesive layer.

10. 10. The image display device according to claim 7, further comprising a camera section at a position corresponding to the through hole of the polarizing plate.

Citation Information

Patent Citations

  • Method for producing differently shaped polarizing plate

    WO2017047510A1